Penerapan Sanksi Pidana Terhadap Tindak Pidana Carding - Bambang Hartono (Law Faculty of Universitas Bandar Lampung, 2013)
Carding a crime has been growing rapidly in Indonesia, while the legal system in Indonesia is still a gap and weak surveillance systems for this crime, where law enforcement is still very alarming. The research problem is how the application of criminal sanctions against criminal carding. Methods of research conducted juridical normative, using secondary data, obtained from literature studies and data analysis with qualitative analysis. Based on the results of the study discusses Application of criminal sanctions against criminal carding device uses existing laws in the Criminal Code, especially in the Article 378 of the KUHP that is about fraud, because carding is a form of fraud as set out in Article 378 of the KUHP.